The Pattern of Islamic Religious Learning In The Tidore Sultanate's Traditional Community - Hendi Sugianto; Nurmala Buamona; Kartini Limatahu; Intan Zilmiani Abdullah; Intan Permata (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2022)
Islam respects local wisdom, as long as local wisdom does not conflict with the teachings of monotheism, Islam always has space for dialogue, then it can merge with the teachings of the local community. The Tidore Sultanate has a strong tradition of Islamic teachings. Although it is not structured as the pattern of Islamic religious learning as usual. The indigenous people of the Tidore Sultanate has a culture of learning that is passed down and rooted so that Islamic teachings remain solid and exist rooted in the indigenous people of the Tidore Sultanate to this day. This study examines the pattern of Islamic religious learning in the Tidore sultanate's traditional community which is rooted to this day, even though without an official curriculum from the sultanate, its teachings become a culture in everyday life.